Suitability of pressmud as an adsorption material in wastewater treatment and as a booster in soil fertility and productivity - Mohamad, Maheera; Osman, Nor Hasni; Abdul Rahim, Mohd Kamarul Irwan (2022)
Pressmud is one of the most abundant wastes produced by the sugarcane industry. However, it has received far too little attention as a reactive material for pollutant removal, although its beneficial effect on soil fertility and crop productivity is well established. This paper investigates the potential of the pressmud to minimize heavy metals migration while boosting soil fertility and productivity. Firstly, the adsorbent was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Field-Emission Scanning Electron Microscopy (FESEM) analyses, which showed the presence of functional groups such as carbonyl, hydroxyl and silica capable of adsorbing metal ions. The cation exchange capacity (CEC) of pressmud was very high, ranging between 44.9-45.2 meq/100g. Along with removal efficiency testing and evaluating breakthrough curve, characterization and adsorption analyses (batch equilibrium and column test) were carried out. The pressmud revealed promising adsorption characteristics, including high organic content (17.62%) and the presence of carbon, which significantly affects its excellent removal effectiveness. Based on the removal efficiency test, pressmud successfully removed the metal ions at the highest value such as Zinc (Zn) at 99.7%. Meanwhile, its breakthrough curve revealed that it efficiently retained all the heavy metals, as these metals did not reach 1 until 10 pore volume (p.v), indicating that pressmud was good material for heavy metals adsorption and soil productivity. This possible use establishes a new cyclical flow for the material and contributes to its minimization and reuse, adhering to circular economy ideas. However, pressmud must be disposed of properly to avoid adverse effects on humans and environments